HUBUNGAN PARITAS DAN KELAINAN LETAK DENGAN KEJADIAN KETUBAN PECAH DINI PADA IBU BERSALINDI UPT PUSKESMAS GAJAH MADA TEMBILAHANTAHUN 2012-2017 - Nurul Indah Sari (Jurnal Kesehatan Husada Gemilang, 2019)
Premature rupture of the membranes is a prematurely rupture of membranes that can occur at the end of pregnancy or long before delivery. There were found, in Gajah Mada Community Health Center, premature rupture of membranes in 30 of 195 maternity women in 2012, 35 of 215 in 2013, 38 of 273 in 2014, 42 of 359 in 2015, 56 of 374 in 2016, and 24 of 338 on January to October 2017. The reason of premature rupture of membranes occurs is not clearly identified, but the factors of premature rupture of membranes enlargement are incompetent cervix, polyhydramnios, gemelli or multiple pregnancies, infections, abnormalities of the fetus position, and parity. This research is to clarify the bond of parity, abnormalities of the fetus position and premature rupture of membrance in maternity womenat Gajah Mada Community Health Center, Tembilahan in 2012-2017. This research is an analytic research with case control. The sample of the research were 340 respondents which consist of case group (215 respondents) and control group (215 respondents). This research uses chi-square and the results prove that there is a correlation between parity and premature rupture of membranes (p value = 0.02) and little clouds and premature rupture of membranes (p value = 0.00). It is greatly expected that health workers advance health promotion about the ANC and the birth control in order to anticipate the little clouds and the parity toward the premature rupture of membranes as early as possible.